Antyczne tradycje o życiu Hippokratesa - Wiszowata, Magdalena (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The ancient traditions of Hippocrates’ life – this paper is concerned with the ancient sources on Hippocrates, an ancient physician, who is considered the father of medicine. This paper is focused on the Bioi of Soranus of Ephesus and Hippocratic pseudoepigraphic letters.
Keywords: Hippocrates; Soranus of Ephesus; pseudoepigraphic letters; ancient biography